Analysis of Determining the Potential for Transit Oriented Development in the Setiabudi District Area, South Jakarta, Indonesia - Taki, Herika Muhamad; Bethany Jaffa Rani; Muhammad Dimas Elvin Putra (UIR PRESS, 2024)
Crucial research into Transit Oriented Development (TOD) in the Setiabudi District of South Jakarta highlights its significance as a burgeoning business center. This study examines the TOD framework, which integrates high-density development with transportation systems to foster an efficient urban environment. Emphasizing pedestrian-friendly spaces and diverse land uses, the research employs a literature review method to outline the criteria and principles of TOD, referencing the ITDP TOD Standard 2017. Additionally, the analysis leverages data from other scholarly articles to assess the potential for TOD in Setiabudi, focusing on radius and distance analyses around key transit hubs using Google Maps and Google Earth. Stations such as LRT Dukuh Atas, LRT Setiabudi, and Bendungan Hilir MRT demonstrate high potential for TOD, while MRT Setiabudi Astra and LRT Kuningan Station show moderate potential. Conversely, Rasuna Said LRT Station exhibits low potential for TOD. The implementation of TOD at high-potential stations could yield significant positive impacts, while MRT Setiabudi Astra and LRT Kuningan Stations present opportunities for enhancement. We find that Rasuna Said LRT Station requires further attention to increase its future potential.